QLEDs: High‐Resolution Pixelated Light Emitting Diodes Based on Electrohydrodynamic Printing and Coffee‐Ring‐Free Quantum Dot Film (Adv. Mater. Technol. 10/2020). Issue 10 (12th October 2020) - Li, Hegeng; Duan, Yongqing; Shao, Zhilong; Zhang, Guannan; Li, Huayang; Huang, YongAn; Yin, Zhouping
Abstract : To satisfy the resolution and film morphology requirements for pixelated quantum dot light emitting diodes (QLEDs), electrohydrodynamic printing (EHD printing) combined with mixed solvent method are presented to realize coffee‐ring‐free pixelated QLEDs with 306 pixels per inch. Their great potential in high‐resolution QLEDs device manufacturing is demonstrated in article number 2000401 by Yongqing Duan, Zhouping Yin and co‐workers.